Effects of the annealing atmosphere on the microstructure and properties of BiFe0.99Zn0.01O3 films. Issue 4 (March 2020) - Zhang, Fengqing; Shen, Peng; Liu, Huiying; Wang, Lingxu; Guo, Xiaodong; Zhao, Xuefeng; Ma, Zhibiao; Tian, Qingbo; Fan, Suhua
Abstract: BiFe0.99 Zn0.01 O3 (BFZO) films were annealed in different atmospheres (Air, N2 and O2 ) on ITO/glass substrates. The influences of the different annealing atmospheres on the oxygen vacancy concentration, microstructure, ferroelectric behavior, leakage current, leakage mechanism, aging and dielectric performance of the BFZO films were studied. The crystallization and grain development for the sample annealed in an O2 atmosphere improved, and the concentrations of the Fe 2+ and oxygen vacancies were the lowest among the samples studied herein. The BFZO film had the lowest leakage current density and the best ferroelectric performance in an O2 annealing atmosphere among the samples studied herein, and the leakage was due to the F-N tunneling effect mechanism. From the perspective of the volume effect, the aging model was established, and the aging mechanism of the BFZO films was discussed in depth. Compared with Air and N2, the annealed film in O2 exhibited no obvious aging.